The Role of Customary Law in Regarding Theft Offenses by Minors - Muh. Bakri; Rika Damayanti; Gustika Sandra; Andi Arfyan Priatama Amar (Journal La Sociale, 2023)
In accordance with the provisions in the articles of the 1945 Constitution of the Republic of Indonesia, it can be said that customary law is recognized for its existence or existence as long as the customary law is still alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia. This research method uses a descriptive research method using a sociological empirical research approach, namely research carried out through field research at the Palakka District police office, as a provider of justice for every problem that occurs in the community, especially in cases of criminal acts. Child theft which was resolved according to custom. This research uses a normative juridical research type, namely research that uses library methods to produce secondary data as main data and basic data, while primary data is in conservative form and interviews as complementary data. So the obstacle encountered by investigators is the very short time factor for the examination process. Of course, with this the problem arises that actually uncovering cases of theft with violence committed by children is quite difficult, especially if the perpetrator carries out the action not alone but in a group. External obstacles are generally technical obstacles, for example because the residence of the perpetrator and witnesses is far from the place of investigation. If in this case there is more than one perpetrator, whose residence is different, then investigators must also often adjust the investigation time.